Heidi Based on a Novel by Johanna Spyri - Spyri, Johanna
Little Heidi (Shirley Temple) is left by her selfish Aunt Dete with her grandfather, a taciturn hermit. Through her plucky charm and positive attitudes, Heidi inspires her grandfather to be nicer and to reach out to the outside world again. But when Aunt Dete steals Heidi back to Frankfurt and leaves her with the stern and vicious Fraulein Rottenmeier, Heidi's grandfather leaves his isolated home to find her and take her back. While it might be arguable whether children will find "Heidi" as entertaining as their parents and grandparents, what is inarguable is the period charm of this 1930's classic. Shirley Temple effortlessly steals every scene she's in (although Arthur Treacher, as the archetypal British butler, certainly comes close), and between the moments of slapstick comedy and cutesy-kid acting, there is also plenty of action in the form of sleigh chases and Grandfather's indomitable yearning to rescue Heidi from the aptly-named Rottenmeier. It is very much a product of its time, but its entertainment value continues to span generations. [www.commonsensemedia.org]